Analysis of the Peaks in the Bucegi Mountains, With Relevance for Sports Tourism Activities - Ioan BÎCA (Cluj University Press, 2024)
Mountain peaks are geographical landmarks that arouse the interest of tourists practicing mountain tourism activities. Summiting a peak is an important reason, both for the views it offers over the landscape and for the personal satisfaction of reaching that point, which requires fitness and will. In addition to the recreational approach, the peaks can also be analyzed from a geo-morphometric point of view, concerning their shape, altitude, and prominence, aspects that matter in sports tourism activities. In this context, the present work aims to analyze the peaks of the Bucegi Mountains and establish their prominence. It is also aimed at the practical side of the problem, materialized through the methodological approach included in the research. Vârfurile munților sunt repere geografice care stârnesc interesul turiștilor care practică activități de turism montan. Adjudecarea unui vârf reprezintă un motiv important, atât pentru perspectivele oferite asupra peisajului, cât și pentru satisfacția personală de a fi atins acel punct, care necesită condiție fizică și voință. Pe lângă abordarea agrementală, vârfurile pot fi analizate și din punct de vedere geomorfometric, cu referire la forma, altitudinea și proeminența acestora, aspecte care contează în activitățile de turism sportiv. În acest context, lucrarea de față își propune să analizeze vârfurile din Munții Bucegi și să stabilească proeminența acestora. De asemenea, este vizată și latură practică a problemei, materializată prin demersul metodologic inclus în cercetare. Cuvinte-cheie: activități sportive în aer liber, turism montan, proeminență montană, înșeuare-cheie, vârf-părinte, sub-vârfuri, descendență genetică, dominanță orometrică, sinclinal suspendat Article history: Received: 2024 April 16; Revised 2024 June 24; Accepted 2024 July 23; Available online: 2024 August 30; Available print: 2024 August 30